PENGARUH PENGGUNAAN MEDIA FILM TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP AL-AZHAR MEDAN - Wita Dwi Payana (Universitas Islam Sumatera Utara, 2020)
This study aims to determine the effect of using film media on the ability to write descriptive text of class VII SMP Al-Azhar Medan. The population of this study amounted to 103 students of SMP Al-Azhar Medan. Samples were taken randomly, namely the experimental class of 32 students. The method used in this study is an experimental one-group pre-test post-test design method. The instrument used to collect data is an essay test. Hypothesis testing is done by using the